Use of Swarna Bindu Prashan in Children - Ganeshrao Sonune, Vishnu; Baliram Bhagile, Jyoti (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This paper presents an overview of use of swarna bindu prashan in children.
Keywords: Swarna prashana samskara; vyadhikshamtva; immunization; immunity booster; intellectual performance